Cultural Festivals and Family Cohesion: Highlighting an Understudied Area - Navabinejad, Shokouh (Journal of Psychosociological Research in Family and Culture, 2024)
Cultural festivals are a significant aspect of social life, providing communities with opportunities for celebration, identity expression, and social cohesion. While there has been extensive research on the economic and social impacts of festivals, there is a pressing need to delve deeper into how these events influence family cohesion and dynamics. This letter aims to highlight the importance of studying the impact of cultural festivals on family relationships, drawing on existing literature to advocate for more comprehensive research in this area. In conclusion, cultural festivals play a significant role in promoting family cohesion by offering shared experiences that reinforce social bonds and cultural identity. However, there is a need for more focused research on how these events impact family dynamics across different cultural contexts. By addressing this gap, we can better understand the potential of cultural festivals to strengthen family relationships and promote social cohesion. We urge researchers and practitioners in the field of psychosociology to prioritize studies on the impact of cultural festivals on family cohesion. Such research will not only contribute to the academic understanding of family dynamics but also inform the design and implementation of festivals to maximize their positive impacts on families.